2000
DOI: 10.1037/0096-1523.26.5.1534
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention: Different mechanisms for central and peripheral temporal precues?

Abstract: The external noise paradigm (Z.-L. Lu & B. A. Dosher, 1998) was applied to investigate mechanisms of spatial attention in location precuing. Observers were precued or simultaneously cued to identify 1 of 4 pseudocharacters embedded in various amounts of external noise. The cues were either central or peripheral. Both central and peripheral precuing significantly reduced threshold in the presence of high external noise (16% and 17.5%). Only peripheral precuing significantly reduced threshold in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
204
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(226 citation statements)
references
References 55 publications
19
204
2
1
Order By: Relevance
“…This conclusion is consistent with the "linking hypothesis," which states that the attentional enhancement of neural firing is interpreted as if the stimulus had a higher contrast (Reynolds & Chelazzi, 2004;Treue, 2004). This proposal is supported by converging evidence from neurophysiological (Martinez-Trujillo & Treue, 2002, Reynolds, Pasternak, & Desimone, 2000, psychophysical (e.g., Carrasco, Ling, & Read, 2004;Carrasco, Penpeci-Talgar, & Eckstein, 2000;Lu & Dosher, 2000) and neuroimaging (Liu, Pestilli, & Carrasco, 2005) studies (for a review, see Carrasco, 2006).…”
Section: Resultssupporting
confidence: 73%
“…This conclusion is consistent with the "linking hypothesis," which states that the attentional enhancement of neural firing is interpreted as if the stimulus had a higher contrast (Reynolds & Chelazzi, 2004;Treue, 2004). This proposal is supported by converging evidence from neurophysiological (Martinez-Trujillo & Treue, 2002, Reynolds, Pasternak, & Desimone, 2000, psychophysical (e.g., Carrasco, Ling, & Read, 2004;Carrasco, Penpeci-Talgar, & Eckstein, 2000;Lu & Dosher, 2000) and neuroimaging (Liu, Pestilli, & Carrasco, 2005) studies (for a review, see Carrasco, 2006).…”
Section: Resultssupporting
confidence: 73%
“…This idea is consistent with the argument that a critical function of attention in perceptual processing is to exclude external noise in the target region (Dosher & Lu, 2000a, 2000bLu & Dosher, 2000;Lu, Lesmes, & Dosher, 2002). Empirical work has also demonstrated that the impact of attention upon perceptual processing can be enhanced by the perceptual difficulty of target processing.…”
Section: Abstract Attentional Blink Rsvp Spread Of Sparingsupporting
confidence: 71%
“…It has been proposed in the attention literature that signal enhancement and external noise reduction are two separate but not mutually exclusive mechanisms underlying attentional effects on visual processing (e.g., Carrasco, 2011;Carrasco, Williams, & Yeshurun, 2002;Dosher & Lu, 2000a;Lu & Dosher, 2000). In this view, sensory enhancement may not be the sole mechanism for effects of working memorydriven attention on visual identification or discrimination.…”
Section: Discussionmentioning
confidence: 99%